The Prevalence of Familial Hypercholesterolemia (FH) in Chinese Patients With Acute Myocardial Infarction (AMI): Data From Chinese Acute Myocardial Infarction (CAMI) Registry - Shi, Hui-Wei; Yang, Jin-Gang; Wang, Yang; Li, Wei; Guo, Yuan-Lin; Gao, Ying; Tang, Yi-Da; Li, Jian-Jun; Wu, Na-Qiong; Yang, Yue-Jin (Frontiers in Cardiovascular Medicine, 2020)
Background: The prevalence of familial hypercholesterolemia (FH) in the patients with acute myocardial infarction (AMI) in China is unclear. Materials and Methods: In China Acute Myocardial Infarction (CAMI) Registry, 13,002 patients with age 18-80 were consecutively enrolled with first-onset AMI who were naïve to statin before admission from January 1st, 2013 to October 31st, 2014. According to Dutch Lipid Clinical Network Criteria (DLCNC), the patients were divided to heterozygous familial hypercholesterolemia (HeFH) (definite/ probable HeFH, possible HeFH ) or non-HeFH group. Results: The number of the patients in the three groups was as following, 62 in definite/probable HeFH group, 484 in possible HeFH group, 12,456 in non-HeFH group. The prevalence of HeFH is 4.2%(including 0.47% of definite/probable HeFH, 3.73% of possible FH) .The average age of onset of first-time AMI was 54±12，56±12，63±12 years old（P<0.0001) in definite/probable HeFH group, possible HeFH group and non-HeFHgroup, respectively. The percentage of Killip III or above (8.1% vs 4.3% vs 6.3%, p=0.1629), cardiac arrest (1.6% vs 0.6% vs 0.9%, p=0.6990), and TIMI 0-2 grade after primary percutaneous cardiac intervention(PCI)( 0% vs 6.8% vs 4.3% , p=0.5866) was not significantly different in definite/probable HeFH group, possible HeFH group and non-HeFH group, respectively. Conclusions: The prevalence of HeFH in Chinese patients with AMI is 4.2%. The patients were significantly younger in HeFH group, when compared with those with non-HeFH. However, no significant differences were found in the severity of clinical manifestations in both HeFH and non-HeFH group.